Exogenous ethanol treatment promotes glycyrrhizin accumulation in aseptically grown Glycyrrhiza uralensis seedlings - Yuto Nishidono; Ken Tanaka (Plant Signaling & Behavior)
Licorice, the dried roots and rhizomes of Glycyrrhiza uralensis Fisch., is one of the most popular herbal medicines used globally. Glycyrrhizin is the primary bioactive component of licorice, exhibiting various pharmacological activities. Herein, we grew G. uralensis seedlings aseptically on a medium in the presence of 0–1% ethanol for 10 weeks, elucidating the effect of exogenous ethanol treatment on plant morphological features and glycyrrhizin accumulation. Treatment with 0.1% exogenous ethanol significantly increased the root fresh weight of G. uralensis seedlings, whereas treatments exceeding 0.5% exogenous ethanol exhibited phytotoxicity. In addition, the application of 0.1% exogenous ethanol significantly promoted glycyrrhizin accumulation in plant roots relative to the control. Overall, these results indicate that dilute exogenous ethanol treatment positively affects root yield and glycyrrhizin accumulation in the roots of aseptically cultured G. uralensis seedlings. The findings of this study may contribute to improving the quality of cultivated G. uralensis.